Supersymmetric minisuperspace models in self-dual loop quantum cosmology - Eder, Konstantin; Sahlmann, Hanno (Journal of High Energy Physics, 2021)
In this paper, we study a class of symmetry reduced models of N = 1 super- gravity using self-dual variables. It is based on a particular Ansatz for the gravitino field as proposed by D’Eath et al. We show that the essential part of the constraint algebra in the classical theory closes. In particular, the (graded) Poisson bracket between the left and right supersymmetry constraint reproduces the Hamiltonian constraint. For the quantum theory, we apply techniques from the manifestly supersymmetric approach to loop quantum supergravity, which yields a graded analog of the holonomy-flux algebra and a natural state space. We implement the remaining constraints in the quantum theory. For a certain subclass of these models, we show explicitly that the (graded) commutator of the supersymmetry constraints exactly reproduces the classical Poisson relations. In particular, the trace of the commutator of left and right supersymmetry constraints reproduces the Hamilton constraint operator. Finally, we consider the dynamics of the theory and compare it to a quantization using standard variables and standard minisuperspace techniques.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Cosmology of Theories beyond the SM; Models of Quantum Gravity; Super-gravity Models